The blindness revolution : Jernigan in his own words - Omvig, Jim H. (Critical concerns in blindness., 2005)
This book recounts the dramatic story of the transformation of the Iowa Commission for the Blind from a verifiably ineffective service agency to perhaps the most outstanding and effective adult service program in the nation in the span of 10 short years. What happened in Iowa was revolutionary, and the character of work with the blind in America and around the world was altered forever--the alternative civil rights-based service model worked. Using Kenneth Jernigan's own writings of Board meeting minutes, reports, and letters, I present the details of the remarkable story from an activist's point of view.